E-Service Intelligence Methodologies, Technologies and Applications - Lu, Jie; Ruan, Da; Zhang, Guangquan (Studies in Computational Intelligence, 2007)
Business organizations and governments are nowadays developing and providing internet based electronic services (e-services) featuring various intelligent functions. E-Service Intelligence integrates intelligent techniques into e-service systems for realizing intelligent internet information searching, presentation, provision, recommendation, online system design, implementation, and assessment to internet users. This book offers a thorough introduction and systematic overview of the new field and covers the state-of-the-art of the research and development in E-Service Intelligence ranging from e-services and/or intelligent techniques to web information presentation, search, and mining, to personalization, privacy, and trust in e-services, to e-service evaluation, optimization and knowledge discovery, and to intelligent e-service system developments.